Prices as an Element of Comparative Studies on People’s Travels in Cities - Dydkowski, Grzegorz; Urbanek, Anna (Communications - Scientific letters of the University of Zilina, 2017)
Ticket prices are one of crucial factors of urban public transport services competitiveness. Ticket prices are expected not only to ensure appropriate revenue for the urban public transport organiser, by they are also an important instrument of cities’ transport policy. The paper is aimed at comparison of urban public transport prices in the largest Polish cities taking into consideration diversified purchasing power as well as the economic potential of city residents and also the competitiveness against the individual car transport. The presented and applied method for comparisons is recommended in particular to compare centres featuring high diversification of the economic potential and of the purchasing power of the population.